Grammatical gender misselection and related errors in French writing by Malaysian students - Abdul Halim, Hazlina; Abd Rahim, Normaliza; Abdul Jabar, Mohd Azidan; Abdul Aziz, Adi Yasran (Universiti Putra Malaysia Press, 2011)
This study aimed to identify grammatical gender misselection errors made by Malaysian students in learning French as a foreign language with regard to writing skills. The study utilized quantitative and qualitative methods of data collection. Data analysis was done by applying the definition of misselection errors by Dulay, Burt and Krashen (1982). A total of 40 subjects participated in this study after 100 hours of learning French. The task consisted of writing two short essays by the subjects, in which they contained different elements of grammatical gender. The results showed that students made misselection errors of French prepositions, verbs, adjectives, articles, and lexis.